Avoidance / approach motivation: Relation with psychological stress and coping - Grakauskas, Žygimantas (Psichologija, 2006)
Self-regulation of behavior maintains purposeful behavior of the people in the presence of changing conditions of environment. Various external and internal stressors hinder from the achievement of aims and raise the condition of psychological stress. One of the most important factors influencing the mode of psychological stress and coping with it cognitive appraisal of the situation. Other important factor – the mode of prevailing motivation. The attitude that two fundamental tendencies – avoidance and approach prevail in the human motivation, has many followers in various branches of psychology. The conducted researches indicate different influence of avoidance/approach motivation on the emotional reactions, cognitive processes and behaviour. We have carried out the research, where we were seeking to assess the relation of the dominating motivation systems to the emotional reactions arising during the stress and the selection of coping strategies. The sensitivity of motivation systems was measured using BIS / BAS scales (Carver and White, 1994). The selection of coping strategies was assessed by “Four factor coping questionnaire” (Grakauskas and Valickas, 2006). For the emotional reactions evaluation 7 points Likert scale was used. Stressful situation was created using hard tasks and limiting the time of their solving. The research results confirmed the relation of different motivation systems (BIS / BAS) domination and different emotional reactions experienced during the stress and the selected stress coping strategie. Behaviour activation system (BAS) positively correlated with positive emotional reactions (joy, relief) and negatively with negative ones – anxiety, sadness, anger (p ≤ 0,01). Behaviour inhibition system (BIS) positively correlated with negative emotional reactions (anxiety, sadness, anger) and negatively with positive (joy, relief) (p ≤ 0,01). Behaviour activation system (BAS) positively correlated with “avoidance” (p ≤ 0,01) and behaviour inhibition system (BIS) with “emotional discharge” (p ≤ 0,01) coping strategy. These results allow to state that there is the ground to speak about different motivation systems, different goals mode and behaviour self regulation types (directed to the achievement of wanted condition or avoidance of the unwanted one) influence on the experienced psychological stress and coping.